Penerapan Pembelajaran Digital Kolaboratif Berbasis SPADA Indonesia - Rizal Arizaldy Ramly Ramly; Ervianti (Jurnal Kependidikan Media, 2026)
Abstract Digital transformation in Indonesian higher education requires learning designs that not only place teaching materials on online platforms, but also strengthen interaction, collaboration, and student engagement. This study examines SPADA Indonesia-based digital collaborative learning through a quantitative model linking collaborative interaction quality, teaching presence, platform quality, digital readiness, student engagement, and perceived learning outcomes. An explanatory survey was conducted with 352 valid student responses using a five-point Likert scale. Data were analyzed through descriptive statistics, construct validity and reliability testing, and hypothesis testing. The results show that all variables were in the high category, with platform quality obtaining the highest mean (M = 4.185; SD = 0.628) and digital readiness the lowest mean (M = 3.826; SD = 0.576). All constructs met validity and reliability criteria, with indicator loadings of 0.716-0.880, AVE of 0.564-0.704, composite reliability of 0.886-0.934, and Cronbach's alpha of 0.844-0.915. Hypothesis testing indicates that collaborative interaction quality had a positive but nonsignificant effect on student engagement (β = 0.056; p = 0.225). In contrast, teaching presence (β = 0.142; p = 0.018), platform quality (β = 0.410; p < 0.001), and digital readiness (β = 0.353; p < 0.001) significantly predicted student engagement, explaining 74.4% of its variance. Student engagement significantly affected perceived learning outcomes (β = 0.743; p < 0.001; R² = 0.553). The findings indicate that platform quality and digital readiness are the dominant determinants of student engagement in SPADA-based digital collaborative learning, while collaborative interaction needs more structured pedagogical design.   Arbaugh, J. B., Cleveland-Innes, M., Diaz, S. R., Garrison, D. R., Ice, P., Richardson, J. C., & Swan, K. P. (2008). Developing a community of inquiry instrument: Testing a measure of the Community of Inquiry framework using a multi-institutional sample. The Internet and Higher Education, 11(3-4), 133-136. https://doi.org/10.1016/j.iheduc.2008.06.003 Ariandini, N., & Ramly, R. A. (2023). Penggunaan multimedia pembelajaran interaktif dalam meningkatkan hasil belajar siswa. Jurnal Kependidikan Media, 12(2), 107-116. Arizaldy, R., & Alfadil, M. T. (2021). The influence of the application of power point learning media on ict learning outcomes. Jurnal Galeri Pendidikan, 1(01), 479. Ayu, S. Virtual Reality (VR) to Revitalize History in Learning. Ayu, S., & Ramly, R. A. (2024). Pengaruh Model Mixed Reality Terhadap Kemampuan Berpikir Kronologis Siswa. PROSIDING UNIVERSITAS KRISTEN INDONESIA TORAJA, 4(1), 30-36. AYU, S., SYATRIANA, E., AKIB, E., NURLINA, N., LATIF, F., & RAMLY, R. (2024). Implementation of Technologocal Pedagogical Content Knowledge (TPACK) in the Malaysian-Indonesian National School. INTERNATIONAL JOURNAL, 11(10), 282. Bach, A., & Thiel, F. (2024). Collaborative online learning in higher education-quality of digital interaction and associations with individual and group-related factors. Frontiers in Education, 9, 1356271. https://doi.org/10.3389/feduc.2024.1356271 Bedenlier, S., Bond, M., Buntins, K., Zawacki-Richter, O., & Kerres, M. (2020). Facilitating student engagement through educational technology in higher education: A systematic review in the field of arts and humanities. Australasian Journal of Educational Technology, 36(4), 126-150. https://doi.org/10.14742/ajet.5477 Bond, M., Buntins, K., Bedenlier, S., Zawacki-Richter, O., & Kerres, M. (2020). Mapping research in student engagement and educational technology in higher education: A systematic evidence map. International Journal of Educational Technology in Higher Education, 17, Article 2. https://doi.org/10.1186/s41239-019-0176-8 Choi, H., & Hur, J. (2023). Passive participation in collaborative online learning activities: A scoping review of research in formal school learning settings. Online Learning, 27(1). https://doi.org/10.24059/olj.v27i1.3414 Darmawati, A., Marwan, M., Suhenrik, P., Ramly, R. A., & Salam, S. (2023). Adaptive Learning in the Independent Curriculum: Integration of Behavioristic, Cognitive and Constructivist Theories in Educational Technology. International Journal of Education, Vocational and Social Science, 2(04), 255-265. Davis, F. D. (1989). Perceived usefulness, perceived ease of use, and user acceptance of information technology. MIS Quarterly, 13(3), 319-340. https://doi.org/10.2307/249008 Dillenbourg, P. (1999). What do you mean by collaborative learning? In P. Dillenbourg (Ed.), Collaborative-learning: Cognitive and computational approaches (pp. 1-19). Elsevier. Fadhilah, F., & Husin, M. (2023). Student readiness on online learning in higher education: An empirical study. International Journal of Instruction, 16(3), 489-504. https://doi.org/10.29333/iji.2023.16326a Garrison, D. R., Anderson, T., & Archer, W. (2000). Critical inquiry in a text-based environment: Computer conferencing in higher education. The Internet and Higher Education, 2(2-3), 87-105. https://doi.org/10.1016/S1096-7516(00)00016-6 Gökoğlu, S., Karaoğlan Yılmaz, F. G., & Yılmaz, R. (2024). Student engagement, Community of Inquiry, and transactional distance in online learning environments: A stepwise multiple linear regression analysis. The International Review of Research in Open and Distributed Learning, 25(4), 107-127. https://doi.org/10.19173/irrodl.v25i4.7660 Hariyanto, D., Yatmono, S., Fajaryati, N., Rahayu, T., & Putro, H. Y. S. (2022). Students e-learning readiness towards Education 4.0: Instrument development. Jurnal Pendidikan Vokasi, 12(3), 266-278. Hastuti, D. N. A. E., Widyanti, R. H. D., Salam, S., Prayogi, A., Alfira, E., & Ramly, R. A. ILMU SEJARAH. Hu, J., & Xiao, W. (2025). What are the influencing factors of online learning engagement? A systematic literature review. Frontiers in Psychology, 16, 1542652. https://doi.org/10.3389/fpsyg.2025.1542652 Johnson, D. W., & Johnson, R. T. (2009). An educational psychology success story: Social interdependence theory and cooperative learning. Educational Researcher, 38(5), 365-379. https://doi.org/10.3102/0013189X09339057 Kaliisa, R., Rienties, B., Mørch, A. I., & Kluge, A. (2022). Social learning analytics in computer-supported collaborative learning environments: A systematic review of empirical studies. Computers and Education Open, 3, 100073. https://doi.org/10.1016/j.caeo.2022.100073 Kalmar, E., Aarts, T., Bosman, E., Ford, C., de Kluijver, L., Beets, J., Veldkamp, L., Timmers, P., Besseling, D., Koopman, J., Fan, C., Berrevoets, E., Trotsenburg, M., Maton, L., van Remundt, J., Sari, E., Omar, L.-W., Beinema, E., Winkel, R., & van der Sanden, M. (2022). The COVID-19 paradox of online collaborative education: When you cannot physically meet, you need more social interactions. Heliyon, 8(1), e08823. https://doi.org/10.1016/j.heliyon.2022.e08823 Kementerian Pendidikan Tinggi, Sains, dan Teknologi. (2025). Penawaran Program Bantuan Pembelajaran Digital Kolaboratif Tahun 2025. SPADA Indonesia. Kementerian Pendidikan Tinggi, Sains, dan Teknologi. (2026). Buku Panduan Penyelenggaraan Pembelajaran Jarak Jauh di Perguruan Tinggi. Direktorat Jenderal Pendidikan Tinggi. Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi. (2024). Penawaran Program Bantuan Pembelajaran Daring Kolaboratif Tahun 2024. SPADA Indonesia. Kurniati, R., & Ramly, R. A. (2022). Development of macromedia flash module in the learning media course faculty of teacher training and education university of pejuang republik Indonesia. MaPan: Jurnal Matematika Dan Pembelajaran, 10(2), 366-384. Lantang, F. A. A., & Ramly, R. A. (2025). Implementation of Goesmart Social Networking Site as a Learning Media In Ict Subjects For Students Class VII. INDONESIAN JOURNAL OF EDUCATIONAL TECHNOLOGY, 4(1), 21-28. Li, L., Zhang, R., & Piper, A. M. (2023). Predictors of student engagement and perceived learning in emergency online education amidst COVID-19: A Community of Inquiry perspective. Computers in Human Behavior Reports, 12, 100326. https://doi.org/10.1016/j.chbr.2023.100326 Moubayed, A., Injadat, M., Shami, A., & Lutfiyya, H. (2020). Student engagement level in an e-learning environment: Clustering using K-means. American Journal of Distance Education, 34(2), 137-156. https://doi.org/10.1080/08923647.2020.1696140 Noer, R. Z., Mustopa, D., Ramly, R. A., Nursalim, M., & Arianto, F. (2023). Landasan Fılosofıs Dan Analısıs Teorı Belajar Dalam Implementası Kurıkulum Merdeka Dı Sekolah Dasar. Jurnal Elementaria Edukasia, 6(4), 1559-1569. Oyarzun, B., & Martin, F. (2023). A systematic review of research on online learner collaboration from 2012-21: Collaboration technologies, design, facilitation, and outcomes. Online Learning, 27(1). https://doi.org/10.24059/olj.v27i1.3407 Oyarzun, B., Kim, S., Maxwell, D., Schaefer, D., & Conklin, S. (2025). The design and effectiveness of online collaborative work. Journal of Computing in Higher Education. https://doi.org/10.1007/s12528-025-09472-2 Pratama, I. G., Hanif, M., Ramly, R. A., & Khotimah, D. K. (2023, July). Pengembangan media belajar pjok berbasis aplikasi smart learning di masa pandemi. In SIPTEK: Seminar Nasional Inovasi Dan Pengembangan Teknologi Pendidikan (Vol. 1, No. 1). Pratama, I. G., Mustaji, M., Mariono, A., & Ramly, R. A. (2026). Analyzing VR-SL Models in Physical Education: a study of Indonesian educational institutions based on the e-readiness model. Retos, 77, 220-237. Ramly, R. A. (2021). Penerapan komunitas belajar melalui aplikasi whatsapp sebagai upaya meningkatkan aktivitas belajar sejarah. Biormatika: Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 7(2), 147-Ã. Ramly, R. A. (2022). Peran Komunikasi Orang Tua Terhadap Pembentukan Karakter Anak Yang Berakhlakul Karimah. Connected: Jurnal Ilmu Komunikasi, 25-37. Ramly, R. A., & Ayu, S. (2022). Pengaruh Media Sosial Terhadap Hasil Belajar Siswa. Jurnal Kependidikan Media, 11(3), 107-119. Ramly, R. A., & Ayu, S. (2025). Pemanfaatan ChatGPT dan AI Sebagai Asisten Pembelajaran: Pelatihan dan Pengembangan Media Pembelajaran. Tongkonan: Jurnal Pengabdian Masyarakat, 4(2), 193-204. Ramly, R. A., & Ilham, I. (2022). Penggunaan Quipper School Terhadap Hasil Belajar Siswa Smp Negeri 2 Campalagian Polewali Mandar. Jurnal Kependidikan Media, 11(2), 65-74. Ramly, R. A., & Latiff, Z. A. (2021). Secondary Teachers Perception on the Effectiveness of Google Classroom As a Learning Medium During Movement Control Order (MCO). Journal of Media and Information Warfare, 14(1), 1-10. Ramly, R. A., Ariaty, E., & Ariandini, N. (2025). IMPLEMENTASI MODEL FLIPPED CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR. Jurnal Kependidikan Media, 14(1), 1-13. Ramly¹, R. A., & Alfadil, M. T. Jurnal Galeri Pendidikan. Ransanz Reyes, E., Arana-Cuenca, A., & Manzanal Martínez, A. I. (2025). Recommendations for designing collaborative activities in online higher education: A systematic review. Journal of Technology and Science Education, 15(1), 4-17. https://doi.org/10.3926/jotse.2818 Rasheed, R. A., Kamsin, A., & Abdullah, N. A. (2020). Challenges in the online component of blended learning: A systematic review. Computers & Education, 144, 103701. https://doi.org/10.1016/j.compedu.2019.103701 Salam, S., Ramly, R. A., Marwan, M., & Irwan, I. (2026). Development and Validation of an Augmented Reality-Based Learning Module to Enhance Historical Understanding in Secondary Education. QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 18(1), 601-616. Salam, S., Suhenrik, P., Ramly, R. A., & Ampa, A. T. (2026). PENGUATAN KESADARAN BUDAYA SISWA MELALUI WORKSHOP BUDAYA LOKAL BERBASIS EDUKASI PARTISIPATIF. PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 4(02), 604-614. Suhendrik, P., Ramly, R. A., Salam, S., Marwan, M., & Irwan, I. (2026). Development of Local Wisdom-Based E-Modules for Strengthening Education and Cultural Tourism in Tanah Toraja Regency. QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 18(1), 617-632. Suhenrik, P., Salam, S., Ramly, R. A., Marwan, M., Alfira, E., & Mustari, U. A. (2025). Teacher Capacity Building in Developing Project-Based Learning Model in Toraja. Jurnal Perjuangan dan Pengabdian Masyarakat: JPPM, 1(3), 30-37. Vygotsky, L. S. (1978). Mind in society: The development of higher psychological processes. Harvard University Press. Yu, Z. (2022). Sustaining student roles, digital literacy, learning achievements, and motivation in online learning environments during the COVID-19 pandemic. Sustainability, 14(8), 4388. https://doi.org/10.3390/su14084388.